PRF1 mutation alters immune system activation, inflammation, and risk of autoimmunity. (August 2021) - Sidore, Carlo; Orrù, Valeria; Cocco, Eleonora; Steri, Maristella; Inshaw, Jamie RJ; Pitzalis, Maristella; Mulas, Antonella; McGurnaghan, Stuart; Frau, Jessica; Porcu, Eleonora; Busonero, Fabio; Dei, Mariano; et al.
Background: Defective alleles within the PRF1 gene, encoding the pore-forming protein perforin, in combination with environmental factors, cause familial type 2 hemophagocytic lymphohistiocytosis (FHL2), a rare, severe autosomal recessive childhood disorder characterized by massive release of cytokines—cytokine storm. Objective: The aim of this study was to determine the function of hypomorph PRF1:p.A91V g.72360387 G > A on multiple sclerosis (MS) and type 1 diabetes (T1D). Methods: We cross-compare the association data for PRF1:p.A91V mutation derived from GWAS on adult MS and pediatric T1D in Sardinians. The novel association with T1D was replicated in metanalysis in 12, 584 cases and 17, 692 controls from Sardinia, the United Kingdom, and Scotland. To dissect this mutation function, we searched through the coincident association immunophenotypes in additional set of general population Sardinians. Results: We report that PRF1:p.A91V, is associated with increase of lymphocyte levels, especially within the cytotoxic memory T-cells, at general population level with reduced interleukin 7 receptor expression on these cells. The minor allele increased risk of MS, in 2903 cases and 2880 controls from Sardinia p = 2.06 × 10 −4, odds ratio OR = 1.29, replicating a previous finding, whereas it protects from T1D p = 1.04 × 10 −5, OR = 0.82. Conclusion: Our results indicate opposing contributions of the cytotoxic T-cell compartment to MS and T1D pathogenesis.